Risk Factors and Reasons for Discharge Against Medical Advice for Newborns With Neonatal Surgical Diseases: A Preliminary Study From a Tertiary Care Hospital in Beijing, China - Yang, Shen; Cai, Siyu; Liao, Junmin; Peng, Xiaoxia; Huang, Jinshi (Frontiers in Pediatrics, 2020)
Background: To identify the risk factors and reasons for discharge against medical advice (DAMA) for newborns with neonatal surgical diseases in a tertiary care hospital in China. Methods：A retrospective study was conducted on all newborn patients admitted to the neonatal surgery department of Beijing Children's Hospital between January 1, 2016 and January 1, 2020. Medical records were compared between DAMA and non-DAMA patients. Univariate and multivariate logistic regression analyses were conducted to identify potentially useful characteristics for predicting DAMA. Results: During the study period, 854 newborns were admitted to the neonatal surgery department. A total of 68 DAMA patients (68/854, 7.96%, 47 boys), with a median age at diagnosis of 1 day (range, from birth to 21 days), were included in this study. After multivariate analysis, we found that emergency admission, age ≤ 5 days, rejection for surgery, and admission to the neonatal intensive care unit were significant independent risk factors for DAMA. According to the electronic medical records, the reasons for DAMA included belief in incurability and concerns about the prognosis of the disease (n = 31), multiple malformations with poor prognosis (n = 8), severe postoperative complications (n = 5), financial difficulties (n = 3), refusal of further examinations (n = 2), assumption of clinical improvement (n = 1), and unknown (n = 18). Conclusions: This preliminary study showed that neonatal surgical patients in critical conditions were high-risk groups for DAMA, and the main possible reasons for DAMA were the parents' belief in incurability and concerns about the prognosis of the disease.